Effective degradation of organic water pollutants by atmospheric non-thermal plasma torch and analysis of degradation process - Bansode, Avinash H.; More, Supriya Eknath; Siddiqui, Ejaz Ahmad; Satpute, Shruti; Ahmad, Absar; Bhoraskar, Sudha V.; Mathe, Vikas L. (Chemosphere, 2017)
The paper reports the use of atmospheric non-thermal plasma torch as a catalyst for degradation of various organic pollutants dissolved in water. A flow of He mixed with air was used to produce the dielectric barrier discharge (DBD), at the tip of the torch, using pulsed electric excitation at 12 kV. The torch, operated at a power of 750 mW/mm², was seen to completely degrade the aqueous solutions of the pollutants namely methylene blue (MB), methyl orange (MO) and rhodamine-B (RB), at around 10⁻⁴ M concentrations, the concentration of polluants is one order higher than of routinely used heterogeneous photocatalytic reactions, within 10 min of irradiation time at room temperature. UV Visible spectra of the organic dye molecules, monitored after different intervals of plasma-irradiation, ranging between 1 and 10 min, have been used as tools to quantify their sequential degradation. Further, instead of using He, only air was used to form plasma plume and used for degradation of organic dye which follow similar trend as that of He plasma. Further, Liquid Chromatography Mass Spectroscopy (LCMS) technique has been used to understand degradation pathway of methylene blue (MB) as a representative case. Total organic carbon (TOC) measurements indicates significant decrease in its content as a function of duration of plasma exposure onto methylene blue as a representative case. Toxicity studies were carried out onto Gram negative Escherichia coli. This indicated that methylene blue, without plasma treatment, shows growth inhibition, whereas with plasma treatment no inhibition was observed.

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films